2021
DOI: 10.3390/plants10030571
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inoculation of Mesorhizobium ciceri with Either Bacillus sp. or Enterobacter aerogenes on Chickpea Improves Growth and Productivity in Phosphate-Deficient Soils in Dry Areas of a Mediterranean Region

Abstract: Biological nitrogen fixation requires a large amount of phosphorus (P). However, most of the soils are P-deficient and the extensive use of P- chemical fertilizers constitute a serious threat to the environment. In this context, two field experiments were carried out to investigate the effect of co-inoculation of Mesorhizobium ciceri with phosphate solubilizing bacteria (PSB), Bacillus sp., and Enterobacter aerogenes, on chickpea as an alternative to chemical nitrogen (N) and phosphorous fertilizers in P-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 93 publications
(88 reference statements)
9
10
0
Order By: Relevance
“…This could be attributed to the multi-strain's ability to effectively nodulate and enhance solubilization of other essential soil minerals such as phosphorus 42 . Similar stimulatory effects on nodulation by coinoculation of rhizobia and PSB has been reported by other authors 43,44,45 .…”
Section: Discussionsupporting
confidence: 90%
“…This could be attributed to the multi-strain's ability to effectively nodulate and enhance solubilization of other essential soil minerals such as phosphorus 42 . Similar stimulatory effects on nodulation by coinoculation of rhizobia and PSB has been reported by other authors 43,44,45 .…”
Section: Discussionsupporting
confidence: 90%
“…The solubilization percentage of our isolates was within the range of 0.4 to 0.8%, supported by the values given previously [26]. Different PSB strains were isolated [27] and reported that the capacity of strains to solubilize P is 37 to 130 ug/ml.…”
Section: Figure 6 Solubilization Index Measured For Seven Days Of Incubationsupporting
confidence: 90%
“…Moreover, citric acid dissolved P more effectively than oxalic and malic acids, according to Hocking [ 49 ] and Hou et al [ 50 ], and organic acids that can form a more stable complex with metal cations will be more successful in releasing aluminum and iron from soil minerals, allowing for more phosphorus to be released. In our study, four genera were determined Pseudomonas , Serratia , Pantoea , and Enterobacter , PSBs are diversified in nature [ 51 ], according to Biswas et al [ 52 ], Sulbaran et al [ 53 ], Bendjelloul et al [ 54 ], and Liu et al [ 36 ]; bacteria belonging to the genera Pseudomonas , Enterobacter , Serratia , and Pantoea are potent PSMs. Moreover, Pseudomonas genera are among the most efficient solubilizers of inorganic phosphate [ 55 ].…”
Section: Discussionmentioning
confidence: 99%